VIII Ukrainian-Polish and III East-European Meeting on Ferroelectrics Physics (Condensed Matter Physics, 2007)
This issue contains Proceedings of the VIII Ukrainian-Polish and III~East-European Meeting on Ferroelectrics Physics (Ukr-Pol 8) held in Lviv on September 4--7, 2006. The Meeting was the continuation of the common Polish-Ukrainian meetings devoted to various problems in physics of ferroelectrics and carried out earlier in Ustron-Zdrój (2004), Uzhgorod-Synjak (2002), Cracow (2000), Dnipropetrovsk (1998), Kudowa Zdrój (1996), Uzhgorod (1994), Wroclaw (1992) and Lviv (1990).